CLONING AND EXPRESSION OF RECOMBINANT PROTEIN OF HUMAN UBIQUITIN, FUSED WITH BIOTIN ACCEPTOR PEPTIDE - Kulyyassov , A.T.; Zhubanova , G.S.; Ramanculov , E.M.; Ogryzko , V.V. (Eurasian Journal of Applied Biotechnology, 2015)
The proximity utilizing biotinylation (PUB) method is based on co-expression within a single cell of recombinant proteins. It involves fusion of the protein of interest with biotin ligase BirA and that of its partner with the biotin acceptor peptide (BAP). The method allows an accurate quantitative assessment of the extent of their interaction in vivo. The aim of this study was to construct a new plasmid vector containing human ubiquitin UbC fused with a BAP and to evaluate its expression in HEK293T cells. To test the model system, we evaluated the protein expression of ubiquitin-BAP and BirA-HP1g (BirA-GFP, control) in HEK293T cells, and we observed a high specificity interaction (biotinylation) in the case of BirA-HP1g versus the control BirA-GFP. In another example of the model system, we observed higher levels of protein-protein interaction of BirA-Tip49 with different ubiquitinated proteins, compared to BirA-Tap54.